Believing in the USA: Derrida, Melville and the Great American Charlatan - Hammerschlag, Sarah (Political theology, 2020)
This essay considers the relationship between the prophet and the charlatan, particularly as they figure in the contemporary American political landscape. It argues that at moments of democratic political crisis these figures arise and reveal the vacancy of sovereignty within the democratic model. The essay treats Herman Melville’s The Confidence-Man along with Jacques Derrida’s writings on democracy and the apocalyptic tone as resources in this endeavor. It considers as well why recent worries over the status of facts in the era of “fake news” have led to critiques of deconstruction.